2013
DOI: 10.1063/1.4827475
|View full text |Cite
|
Sign up to set email alerts
|

Shell model of BaTiO3 derived from ab-initio total energy calculations

Abstract: A shell model for ferroelectric perovskites fitted to results of first-principles density functional theory (DFT) calculations is strongly affected by approximations made in the exchange-correlation functional within DFT, and in general not as accurate as a shell model derived from experimental data. We have developed an isotropic shell model for BaTiO 3 based on the PBEsol exchange-correlation functional [Perdew et al., Phys. Rev. Lett. 100, 136406 (2008)], which was specifically designed for crystal properti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 30 publications
4
23
0
Order By: Relevance
“…We use the isotropic, an-harmonic core-shell model potential for BaTiO 3 (presented below) that has been fitted to results of first-principles density functional theory calculations with a modified generalized gradient approximation 28 . All the simulations are performed with 60 × 10 × 10 unit cells under periodic boundary conditions.…”
Section: Methodsmentioning
confidence: 99%
“…We use the isotropic, an-harmonic core-shell model potential for BaTiO 3 (presented below) that has been fitted to results of first-principles density functional theory calculations with a modified generalized gradient approximation 28 . All the simulations are performed with 60 × 10 × 10 unit cells under periodic boundary conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Among these methods, MD simulations with shell models fitted to firstprinciples calculations are sufficient for predicting the behavior of pure compounds and solid solutions. [35,37,38] configurations to analyze the influence of local order on the ferroelectric properties. [48] In the current work, we use a shell model fitted to first-principles calculations to study the electric field-induced phase transition and the EC effect at room temperature with respect to concentration and electric field magnitude in a PMN-PT solid-solution single crystal.…”
Section: Introductionmentioning
confidence: 99%
“…[24,28] The mechanism of the EC enhancement near the MPB region is associated with an easy path for polarization rotation. First-principles calculations, [30][31][32][33][34] atomic-level MD simulations [35][36][37][38], Monte-Carlo simulations [39] and phenomenological Landau theories [40,41] have been used to study the electric field-induced phase transition in ferroelectrics. Among these methods, MD simulations with shell models fitted to firstprinciples calculations are sufficient for predicting the behavior of pure compounds and solid solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The test case involves a Perovskite crystalline structure barium titanate (BaTiO 3 ), and a rocksalt crystalline structure magnesia (MgO). Both are modeled using the Coulomb-Buckingham potential [19,32,33,34]:…”
Section: Materials Choicementioning
confidence: 99%
“…Furthermore, an Atomistic Field Theory (AFT) based [18] formulation is presented to efficiently calculate the distribution of the polarization, the electric potential and field and the charge density given the state of the constituent atoms of the surface lattices. MD simulations are used to simulate the lattice deformations resulting from the contact of Perovskite crystalline structure Barium Titanate (BaTiO 3 ) and Magnesia (MgO) because these materials have well established models in the literature [19,20]. It is shown that lattice deformations occur when the two materials are placed in sufficient proximity for the atomic interactions across the boundary to become strong enough to alter the atomic positions and form the surface dipoles.…”
Section: Introductionmentioning
confidence: 99%